The Coach-Athlete Relationship in Football and its Implications for Achievement Motivation - Mahesa Agustira; Nurlan Kusmaedi; Finaldhi Palgunadhi (Universitas Negeri Semarang, 2026)
This study aims to explore the relationship between coach-athlete relationships and achievement motivation in football players. This research is based on the significance of quality interaction between coaches and athletes as a psychological element that influences motivation, satisfaction in training, and athletic performance. This study applied a quantitative method with a descriptive correlational design, involving 40 football athletes from the Indonesian University of Education's Student Activity Unit Football. The measurement tools used include the Coach-Athlete Relationship Questionnaire (CART-Q) to assess commitment, closeness, and complementarity, as well as the Sport Motivation Scale II (SMS-II) to measure six aspects of motivation. Findings from descriptive analysis indicate that the level of coach-athlete relationships is high and consistent across all dimensions of CART-Q. Motivation evaluation shows the dominance of autonomous motivation, reflected in high scores on intrinsic motivation, integrated regulation, and identified regulation, with low levels of amotivation. Pearson's correlation test revealed a positive and significant relationship between coach-athlete relationships and achievement motivation (r = 0.438; p < 0.01). These findings imply that the better the quality of the relationship formed between coaches and athletes, the greater the athletes' motivation to achieve. This study confirms that a high-quality coach-athlete relationship serves as a crucial factor in building achievement motivation, so coaches are expected to improve communication, trust, and emotional support during the coaching process.